A Mixed-Methods Evaluation of Patient Education Materials for Colorectal Cancer. Issue 10 (7th September 2021) - Kang, Ravinder; Saunders, Catherine H.; Carpenter-Song, Elizabeth A.; Moore, Kayla O.; Trooboff, Spencer W.; Columbo, Jesse A.; Goodney, Philip P.; Wong, Sandra L.; Joga Ivatury, Srinivas
Abstract : BACKGROUND: Patient education materials are created by professional organizations to inform patients about their disease and its treatment. However, it remains unclear if these materials are appropriate for patients. OBJECTIVE: This study aims to broadly evaluate the education materials for patients with colorectal cancer. DESIGN: Patient education materials from the National Comprehensive Cancer Network, the National Cancer Institute, and the American Society of Colon and Rectal Surgeons were assessed quantitatively by using 1) the Flesch-Kincaid readability formula and 2) the Patient Education Material Assessment Tool. The Patient Education Material Assessment Tool scores materials in 2 domains: understandability and actionability. These materials were further evaluated qualitatively via an exploratory focus group with patients and their caregivers (n = 5) and semi-structured interviews with board-certified/eligible colorectal surgeons (n = 10). SETTING: This study was conducted at academic centers and a regional professional society meeting. PARTICIPANTS: The mean patient age was 63. Most surgeons (8/10) practiced in an academic setting, and 4/10 were female. MAIN OUTCOME MEASURES: The primary outcomes measured were reading grade level and domain scores for the Patient Education Material Assessment Tool. Qualitative data were recorded, transcribed, and coded. Themes were generated through data interpretation and data reduction. RESULTS: Materials ranged from 7th to 11th grade reading level. National Comprehensive Cancer Network materials scored highest for understandability (92.2% ± 6.1%, mean ± SD), followed by National Cancer Institute (84.0% ± 6.6%) and American Society of Colon and Rectal Surgeons (82.2% ± 6.3%) materials. Actionability scores varied; the National Comprehensive Cancer Network materials scored 82.5% ± 1.7%, whereas the National Cancer Institute and American Society of Colon and Rectal Surgeons materials scored 23.3% ± 6.7% and 50.0% ± 8.2%. Critical gaps were identified in the content of these materials. Patients wanted more information about self-care, both emotional and physical. Specifically, patients sought details about postoperative bowel function. Whereas surgeons wanted information about the typical hospital course and recovery, all wanted materials to be customizable. LIMITATIONS: A limited number of materials were reviewed, and patient focus groups were exploratory. CONCLUSIONS: Commonly available printed education materials for colorectal cancer are written at a high reading grade level, vary in their usability, and neglect important details about postoperative recovery. See Video Abstract at http://links.lww.com/DCR/B535 . EVALUACIÓN DE MÉTODOS MIXTOS DE MATERIALES EDUCATIVOS PARA PACIENTES SOBRE CÁNCER COLORECTAL: ANTECEDENTES: Los materiales educativos para pacientes son creados por organizaciones profesionales para informar a los pacientes sobre su enfermedad y su tratamiento. Sin embargo, no está claro si estos materiales son apropiados para los pacientes. OBJETIVO: Evaluar ampliamente los materiales para el cáncer colorrectal. DISEÑO: Los materiales educativos para pacientes de la Red Nacional Integral del Cáncer (NCCN), el Instituto Nacional del Cáncer (NCI) y la Sociedad Americana de Cirujanos de Colon y Recto (ASCRS) se evaluaron cuantitativamente utilizando (1) la fórmula de legibilidad de Flesch-Kincaid y (2) la herramienta de evaluación de material educativo para pacientes. La Herramienta de evaluación de materiales educativos para pacientes califica los materiales en dos dominios: comprensibilidad y viabilidad. Estos materiales fueron evaluados cualitativamente a través de un grupo de enfoque exploratorio con pacientes y sus cuidadores ( n = 5) y entrevistas semiestructuradas con cirujanos colorrectales certificados o elegibles para certificación por el consejo ( n = 10). ESCENARIO: Centros académicos y un encuentro regional de una sociedad profesional. PACIENTES: La edad media de los pacientes fue de 63 años. La mayoría de los cirujanos (8/10) practicaban en un entorno académico, y 4/10 eran mujeres. PRINCIPALES MEDIDAS DE RESULTADO: Nivel de grado de lectura y puntajes de dominios para la Herramienta de evaluación de materiales educativos para pacientes. Los datos cualitativos se registraron, transcribieron y codificaron. Los temas se generaron mediante la interpretación y la reducción de datos. RESULTADOS: Los materiales variaron desde el nivel de lectura del 7° al 11° grado. Los materiales de la NCCN obtuvieron la puntuación más alta en comprensibilidad (92.2 ± 6.1%, media ± DE), seguidos por los materiales de NCI (84.0 ± 6.6%) y ASCRS (82.2 ± 6.3%). Los puntajes de viabilidad variaron; Los materiales de NCCN obtuvieron una puntuación de 82.5 ± 1.7%, mientras que los materiales de NCI y ASCRS obtuvieron una puntuación de 23.3 ± 6.7% y 50.0 ± 8.2%, respectivamente. Se identificaron lagunas críticas en el contenido de estos materiales. Los pacientes querían más información sobre el autocuidado, tanto emocional como físico. Específicamente, los pacientes buscaron detalles sobre la función intestinal posoperatoria. Mientras que los cirujanos querían información sobre el curso hospitalario típico y la recuperación, y todos querían que los materiales fueran personalizables. LIMITACIONES: Se revisó una cantidad limitada de materiales y los grupos de enfoque de pacientes fueron exploratorios. CONCLUSIONES: Los materiales educativos impresos comúnmente disponibles para el cáncer colorrectal están escritos a un alto nivel de grado de lectura, varían en su usabilidad y omiten detalles importantes sobre la recuperación postoperatoria. Consulte Video Resumen en http://links.lww.com/DCR/B535 .